Strategic orientation and performance in Dedicated Biotechnology Firms - Hynes, Niki; Mollenkopf, D. (Inderscience Enterprises Ltd, 2006)
Studies have shown that market orientation has been associated with superior performance in several industries. However Dedicated Biotechnology Firms (DBFs), and other technology-based firms operate in turbulent environments where knowledge, alliances and being first to establish technical leadership are paramount. The importance of technological orientation is exaggerated. This international empirical study examines the relationship between market and technological orientation and firm performance, including new product success. A new scale to capture technological orientation is developed and validated but no relationship between this and firm performance is found. Results show the cross-cultural validity of the scale for market orientation and positive association between some measure of performance and the level of market orientation.